Concentrations and fluxes of biogenic volatile organic compounds above a Mediterranean macchia ecosystem in western Italy - Davison, B.; Taipale, R.; Langford, B.; Misztal, P.; Fares, S.; Matteucci, G.; Loreto, F.; Cape, J. N.; Rinne, J.; Hewitt, C. N. (BIOGEOSCIENCES, 2009)
Emission rates and concentrations of biogenic volatile organic compounds (BVOCs) were measured at a Mediterranean coastal site at Castelporziano, approximately 25 km south-west of Rome, between 7 May and 3 June 2007, as part of the ACCENT-VOCBAS field campaign on biosphere-atmosphere interactions. Concentrations and emission rates were measured using the disjunct eddy covariance (DEC) method utilizing three different proton transfer reaction mass spectrometers (PTR-MS) so allowing a comparison between the instruments. The high resolution data from the PTR-MS instruments considerably enhances the original BEMA measurements of the mid 1990s. Depending on the measurement period, the volume mixing ratios were in the range 1.6-3.5 ppbv for methanol, 0.44-1.3 ppbv for acetaldehyde, 0.96-2.1 ppbv for acetone, 0.10-0.14 ppbv for isoprene, and 0.13-0.30 ppbv for monoterpenes. A diurnal cycle in mixing ratios was apparent with daytime maxima for methanol, acetaldehyde, acetone, and isoprene. The fluxes ranged from 370-440 mu g m(-2) h(-1) for methanol, 180-360 mu g m(-2) h(-1) for acetaldehyde, 180-450 mu g m(-2) h(-1) for acetone, 71-290 mu g m(-2) h(-1) for isoprene, and 240-860 mu g m(-2) h(-1) for monoterpenes. From the measured flux data (7 May-3 June) an average basal emission rate for the Macchia vegetation was calculated of 430 mu g m(-2) h(-1) for isoprene and 1100 mu g m(-2) h(-1) for monoterpenes.
APSAPSThe following values have no corresponding Zotero field: pub-location: BAHNHOFSALLEE 1E, GOTTINGEN, 37081, GERMANY publisher: COPERNICUS GESELLSCHAFT MBH
Keywords: BVOCS; Emission rates; Mediterranean; Monoterpenes

The influence of leaf water content and isoprenoids on flammability of some Mediterranean woody species - De Lillis, Manuela; Bianco, Pietro Massimiliano; Loreto, Francesco (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2009)
The impact of water content and isoprenoids on leaf flammability was studied. Field and laboratory experiments were carried out on monoterpene-emitting evergreen broad-leaved species (Quercus ilex, Quercus suber); a needle-leaved species (Pinus halepensis) that emits and stores monoterpenes; an evergreen species (Myrtus communis) that emits isoprene but stores monoterpenes; and a deciduous species (Quercus pubescens) that emits isoprene. Photosynthesis, leaf water content (LWC) and isoprenoid emission were measured. Isoprenoid content was calculated. Temperatures of visible smoke, incandescence and flame appearance were recorded. The LWC significantly correlated with both photosynthesis and isoprenoid emissions. Linear correlation and factorial analysis revealed a positive correlation between temperature of flame appearance and LWC and a negative relationship between temperature of flame appearance and isoprenoid emission. Multiple regression analysis indicated that the temperature of flame appearance was reduced in broadleaved monoterpene-emitting species. In monoterpene emitters, the temperature of flame appearance depended for similar to 65% on LWC, whereas monoterpene emissions explained similar to 35% of the dependency. P. halepensis and M. communis, storing high levels of isoprenoids, ignited at high humidity. The results may be explained if isoprenoids indeed facilitate leaf ignition but, being dissolved in water, isoprenoids are also an indicator of a high water content that decreases flammability.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: CSIRO PUBLISHING
Keywords: fire; flammability phases; Monoterpenes; photosynthesis

Stomatal uptake and stomatal deposition of ozone in isoprene and monoterpene emitting plants - Fares, S.; Loreto, F.; Kleist, E.; Wildt, J. (Plant Biology, 2008)
Volatile isoprenoids were reported to protect plants against ozone. To understand whether this could be the result of a direct scavenging of ozone by these molecules, the stomatal and non-stomatal uptake of ozone was estimated in plants emitting isoprene or monoterpenes. Ozone uptake by holm oak (Quercus ilex, a monoterpene emitter) and black poplar (Populus nigra, an isoprene emitter) was studied in whole plant enclosures (continuously stirred tank reactors, CSTR). The ozone uptake by plants was estimated measuring ozone concentration at the inlet and outlet of the reactors, after correcting for the uptake of the enclosure materials. Destruction of ozone at the cuticle or at the plant stems was found to be negligible compared to the ozone uptake through the stomata. For both plant species, a relationship between stomatal conductance and ozone uptake was found. For the poplar, the measured ozone losses were explained by the uptake of ozone through the stomata only, and ozone destruction by gas phase reactions with isoprene was negligible. For the oak, gas phase reactions of ozone with the monoterpenes emitted by the plants contributed significantly to ozone destruction. This was confirmed by two different experiments showing a) that in cases of high stomatal conductance but under low CO2 concentration, a reduction of monoterpene emission was still associated with reduced O3 uptake; and b) that ozone losses due to the gas phase reactions only can be measured when using the exhaust from a plant chamber to determine the gas phase reactivity in an empty reaction chamber. Monoterpenes can therefore relevantly scavenge ozone at leaf level contributing to protection against ozone.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: isoprene; Monoterpenes; Ozone uptake; photosynthesis; reaction chambers; Stomatal conductance

Seasonal soil VOC exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - ASENSIO, D.; Penuelas, J.; Ogaya, R.; Llusia, J. (Atmospheric Environment, 2007)
Available information on soil volatile organic compound (VOC) exchange, emissions and uptake, is very scarce. We here describe the amounts and seasonality of soil VOC exchange during a year in a natural Mediterranean holm oak forest growing in Southern Catalonia. We investigated changes in soil VOC dynamics in drought conditions by decreasing the soil moisture to 30% of ambient conditions by artiﬁcially excluding rainfall and water runoff, and predicted the response of VOC exchange to the drought forecasted in the Mediterranean region for the next decades by GCM and ecophysiological models. The annual average of the total (detected) soil VOC and total monoterpene exchange rates were 3.273.2 and 0.470.3 mg m 2 h 1 , respectively, in control plots. These values represent 0.003% of the total C emitted by soil at the study site as CO2 whereas the annual mean of soil monoterpene exchange represents 0.0004% of total C. Total soil VOC exchange rates in control plots showed seasonal variations following changes in soil moisture and phenology. Maximum values were found in spring (1778 mg m 2 h 1 ). Although there was no signiﬁcant global effect of drought treatment on the total soil VOC exchange rates, annual average of total VOC exchange rates in drought plots resulted in an uptake rate (0.571.8 mg m 2 h 1 ) instead of positive net emission rates. Larger soil VOC and monoterpene exchanges were measured in drought plots than in control plots in summer, which might be mostly attributable to autotrophic (roots) metabolism. The results show that the diversity and magnitude of monoterpene and VOC soil emissions are low compared with plant emissions, that they are driven by soil moisture, that they represent a very small part of the soil-released carbon and that they may be strongly reduced or even reversed into net uptakes by the predicted decreases of soil water availability in the next decades. In all cases, it seems that VOC ﬂuxes in soil might have greater impact on soil ecology than on atmospheric chemistry
Keywords: climate change; Drought; Mediterranean holm oak forest; Monoterpenes; Soil CO2 flux; Soil VOC exchange

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

The capacity for thermal protection of photosynthetic electron transport varies for different monoterpenes in Quercus ilex - Copolovici, L. O.; Filella, I.; Llusia, J.; Niinemets, U.; Penuelas, J. (PLANT PHYSIOLOGY, 2005)
Heat stress resistance of foliar photosynthetic apparatus was investigated in the Mediterranean monoterpene-emitting evergreen sclerophyll species Quercus ilex. Leaf feeding with fosmidomycin, which is a specific inhibitor of the chloroplastic isoprenoid synthesis pathway, essentially stopped monoterpene emission and resulted in the decrease of the optimum temperature of photosynthetic electron transport from approximately 38 degrees C to approximately 30 degrees C. The heat stress resistance was partly restored by fumigation with 4 to 5 nmol mol(-1) air concentrations of monoterpene alpha-pinene but not with fumigations with monoterpene alcohol alpha-terpineol. Analyses of monoterpene physicochemical characteristics demonstrated that alpha-pinene was primarily distributed to leaf gas and lipid phases, while alpha-terpineol was primarily distributed to leaf aqueous phase. Thus, for a common monoterpene uptake rate, alpha-terpineol is less efficient in stabilizing membrane liquid-crystalline structure and as an antioxidant in plant membranes. Furthermore, alpha-terpineol uptake rate ( U) strongly decreased with increasing temperature, while the uptake rates of alpha-pinene increased with increasing temperature, providing a further explanation of the lower efficiency of thermal protection by alpha-terpineol. The temperature-dependent decrease of alpha-terpineol uptake was both due to decreases in stomatal conductance, g(w), and increased volatility of alpha-terpineol at higher temperature that decreased the monoterpene diffusion gradient between the ambient air (F-A) and leaf (F-I; U=g(w)\{[\}F-A - F-I]). Model analyses suggested that alpha-pinene reacted within the leaf at higher temperatures, possibly within the lipid phase, thereby avoiding the decrease in diffusion gradient, F-A-F-I. Thus, these data contribute to the hypothesis of the antioxidative protection of leaf membranes during heat stress by monoterpenes. These data further suggest that fumigation with the relatively low atmospheric concentrations of monoterpenes that are occasionally observed during warm windless days in the Mediterranean canopies may significantly improve the heat tolerance of nonemitting vegetation that grows intermixed with emitting species.
APSAPSThe following values have no corresponding Zotero field: pub-location: 15501 MONONA DRIVE, ROCKVILLE, MD 20855 USA publisher: AMER SOC PLANT BIOLOGISTS
Keywords: foliar photosynthesis; heat stress resistance; Mediterranean; Monoterpenes; Quercus ilex L.

Linking isoprene with plant thermotolerance, antioxidants and monoterpene emissions - Penuelas, J.; Llusia, J.; ASENSIO, D.; MUNNÉ-BOSCH, S. (Plant, Cell & Environment, 2005)
The purpose of the present study was to test the possible plant thermotolerance role of isoprene and to study its relationship with non-enzymatic antioxidants and terpene emissions. The gas exchange, chlorophyll fluorescence, extent of photo- and oxidative stress, leaf damage, mechanisms of photo- and antioxidant protection, and terpene emission were measured in leaves of Quercus ilex seedlings exposed to a ramp of temperatures of 5 °C steps from 25 to 50 °C growing with and without isoprene (10 µL L−1) fumigation. The results showed that isoprene actually conferred thermotolerance (shifted the decrease of net photosynthetic rates from 35 to 45 °C, increased Fv/Fm at 50 °C from 0.38 to 0.65, and decreased the leaf area damaged from 27 to 15%), that it precluded or delayed the enhancement of the antioxidant non-enzymatic defence conferred by α-tocopherol, ascorbic acid or β-carotene consumption in response to increasing temperatures, and that it decreased by approximately 70% the emissions of monoterpenes at the highest temperatures. This suggests that there are inducible mechanisms triggered by the initial stages of thermal damage that up-regulate these antioxidant compounds at high temperatures and that these mechanisms are somehow suppressed in the presence of exogenous isoprene, which seems to already exert an antioxidant-like behaviour.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: antioxidants; ascorbic acid; fumigation; Fv/Fm; high temperatures; isoprene; Monoterpenes; photosynthetic rates; thermotolerance; zeaxanthin; α-tocopherol; β-carotene

Direct and indirect impacts of fire on isoprenoid emissions from Mediterranean vegetation - Alessio, G. A.; Lillis, M. De; Fanelli, M. (Functional Ecology, 2004)
1. Fire is often associated with episodes of air pollution, possibly involving the release of biogenic isoprenoids (isoprene and monoterpenes). The direct and indirect impacts of ﬁre on isoprenoid emission by plants of the Mediterranean vegetation were studied. Leaves of Arbutus unedo, Phillyrea latifolia, Cistus incanus, Cistus mospeliensis, Pistacia lentiscus, Quercus ilex, Quercus suber, Quercus pubescens, Myrtus communis and Pinus halepensis were exposed to direct ﬁre or to the ﬁre-consequent wave of elevated temperature. 2. Half the tested plant species did not emit isoprenoids and the treatments did not induce isoprenoid emission. In contrast, isoprene was emitted by intact leaves of Q. pubescens and M. communis, while monoterpenes were emitted by intact leaves of Q. ilex, Q. suber and P. halepensis. 3. The two treatments rapidly reduced isoprene emission by isoprene-emitting species and monoterpene emission by Quercus spp. This inhibition was associated with photosynthetic inhibition, and recovery was seen in Quercus spp. within days of treatment. Recovery was also associated with the recovery of photosynthesis, suggesting that emitted isoprenoids continue to be formed predominantly from photosynthetic intermediates after a ﬁre episode. 4. In Q. pubescens leaves, however, recovery from the elevated-temperature treatment caused a sustained increase of isoprene emission which was not mirrored by a similar increase in photosynthesis. Whether this represents the induction of alternative metabolic pathways or an increase of the ﬂux of photosynthetic carbon in the isoprene pathway is not known. Isoprene-emitting species in areas surrounding ﬁre may emit a substantially larger hydrocarbon ﬂux for several days after ﬁre. 5. The elevated-temperature treatment induced the emission of α-pinene from Myrtus leaves, and the ﬁre treatment stimulated the emission of several monoterpenes from Pinus needles. The emission began to decrease within minutes in Myrtus, while it increased within the ﬁrst 100 min in Pinus, where it was detectable the day after the event although the ﬂux was smaller than in prestressed needles. 6. Exposure to ﬁre and to the associated elevated temperature may induce bursts of monoterpenes from plants that regularly do not emit these compounds and temporarily increase the load of monoterpenes in the atmosphere by pine species. These emissions may contribute to photochemical reactions involved in smog and ozone formation
Keywords: isoprene; Mediterranean plant species; Monoterpenes; Ozone; photosynthesis; Stomatal conductance; ﬁre ecology

Isoprenoid emissions of Quercus spp. (Q. suber and Q. ilex) in mixed stands contrasting in interspecific genetic introgression - Staudt, Michael; Mir, Celine; Joffre, Richard; Rambal, Serge; Bonin, Aurelie; Landais, Damien; Lumaret, Roselyne (New Phytologist, 2004)
• Among oak species, Quercus ilex is classiﬁed as a monoterpene emitter and Q. suber is mainly known as a nonisoprenoid emitter. The extent and origin of this diversiﬁcation is unknown. • We examined intra- and interspeciﬁc emission variability in two mixed stands which differed in their level of hybridization and reciprocal genetic introgression based on variations in cytoplasmic (chloroplast DNA) and nuclear (allozyme) markers. • At both sites all trees identiﬁed as Q. ilex, or as recent descendants from Q. ilex × Q. suber hybrids, emitted monoterpenes. Of Q. suber trees (genetically introgressed or not by Q. ilex), 91% were also monoterpene emitters, and the remainder nonemitters. One tree identiﬁed as a Q. canariensis × Q. ilex hybrid emitted both isoprene and monoterpenes. Compared with Q. ilex, the standard emission rate of Q. suber was higher in summer and lower in autumn. Both species emitted the same monoterpenes, proportions of which showed signiﬁcant intra- and interspeciﬁc variability. • The results suggest that Q. suber populations in the French Mediterranean intrinsically emit monoterpenes, and that gene ﬂow between oak species contributes to diversiﬁcation of emission signatures.
Keywords: basal emission rate; chemotaxonomy; chemotypes; Evergreen oaks; genetic introgression; isoprene; Monoterpenes; VOC (volatile organic compound) emissions.

Linking photorespiration, monoterpenes and thermotolerance in Quercus - Penuelas, Josep; Llusia, Joan (New Phytologist, 2002)
* • The functions of two important plant processes, photorespiration and monoterpene production remain controversial. Here, we investigated one possible function, that of protection of plants from photodamage at high temperatures. * • Fluorescence, reflectance, monoterpene concentrations and visual leaf damage were measured in Quercus ilex seedlings exposed to temperature increases from 25 to 50°C (in 5°C steps) under photorespiratory (21% O 2 ) or nonphotorespiratory (2% O 2 ) atmospheres, and under control or terpene fumigation conditions. * • Lower variable to maximum fluorescence ratio (Fv : Fm: potential photochemical efficiency of photosystem II, PSII) and electron transport rate (ETR) were found in nonphotorespiratory conditions at temperatures greater than 35°C. Monoterpene concentrations were also lower, and leaf damage greater, in the low O 2 atmospheres. Monoterpene fumigation, which increased the foliar terpene concentrations by two- to four-fold, increased the photochemical efficiency between 35°C and 50°C, and decreased leaf damage, only under the nonphotorespiratory conditions. * • These results provide evidence that: photorespiration decreases photodamage, especially at high temperatures; photorespiration increases monoterpene production; plants are able to acquire exogenous monoterpenes and the acquisition response to temperature follows the stomatal conductance response; and monoterpenes can replace photorespiration in protection from photodamage at high temperatures, possibly by scavenging oxygen-reactive species, but they do not provide additional thermotolerance.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: electron transport rate (ETR); fumigation; Fv : Fm; limonene; Monoterpenes; photochemical reflectance index (PRI); photorespiration; thermotolerance; α-pinene

Fumigation with exogenous monoterpenes of a non-isoprenoid-emitting oak (Quercus suber): monoterpene acquisition, translocation, and effect on the photosynthetic properties at high temperatures - Delfine, Sebastiano; Csiky, Olav; Seufert, Guenther; Loreto, Francesco (New Phytologist, 2000)
We tested if fumigation with exogenous monoterpenes might induce thermotolerance in leaves of an oak species (Quercus suber) which does not form and emit isoprenoids. To understand if exogenous monoterpene fumigation results in internal accumulation of monoterpenes, a physical method of monoterpene extraction was used. The internal content of monoterpenes increased in concert with increasing fumigation doses. This unambiguously demonstrated acquisition of exogenous monoterpenes. We exposed fumigated Q. suber leaves to two cycles of increasing temperatures from 35 to 55°C at 5°C steps. When leaves were exposed to a low dose of exogenous monoterpenes, yielding an internal content similar to that endogenously formed in the leaves of the monoterpene- emitter Q. ilex, no clear improvement in thermotolerance was found. When leaves were exposed to a high dose of exogenous monoterpenes, yielding an internal content of about ®ve fold the endogenous pool of Q. ilex, but comparable with the expected content following stress-induced stomatal closure, photosynthesis inhibition at high temperatures was attenuated. This eﬀect was observed only at temperatures !45°C during the ®rst cycle, but at all temperatures between 35 and 55°C when plants were exposed to two cycles of high temperatures. Monoterpenes were still found in the leaves of Q. suber 12 h after ending the fumigation. Monoterpenes were also found in non-fumigated leaves distant up to 45 cm from the fumigated leaves. If monoterpenes make the photosynthetic apparatus more resistant to high temperatures, the eﬀect might not be limited to the fumigated leaves and might be persistent after fumigation.
Keywords: isoprenoid emission; Monoterpenes; photosynthesis; Quercus suber; thermotolerance

Terpenoid emissions of Mediterranean oaks and their relation to taxonomy - Csiky, O.; Seufert, G. (ECOLOGICAL APPLICATIONS, 1999)
This paper presents results of a laboratory screening study of biogenic emissions from Mediterranean oak species. The experiment aimed at improving our understanding of oak contributions to overall emissions of volatile organic compounds and to the atmospheric chemistry in the Mediterranean area. We measured type and amount of terpenoid emissions (isoprene, mono- and sesquiterpenes) under standard conditions of light and temperature from 14 different Quercus species of Mediterranean and American origin. Tree saplings were exposed in a controlled environment chamber, and leaf-level trace-gas exchange was analyzed with a minicuvette system and gas chromatography, to study the relation between the emission types and emission spectra found and the taxonomy of Quercus. The holarctic group Lepidobalanus and the North American groups Erythrobalanus and Protobalanus were found to be strong isoprene emitters. The Eurasian oak group Sclerophyllodrys emits monoterpenes; Cerris include mostly non-emitters, but also an isoprene and a monoterpene emitter has been found in this group. Results are discussed with respect to their implications for presently used emission scenarios.
The following values have no corresponding Zotero field: pub-location: 1707 H ST NW, STE 400, WASHINGTON, DC 20006-3915 USA publisher: ECOLOGICAL SOC AMER
Keywords: atmospheric chemistry; BEMA (Biogenic Emissions in the Mediterranean Area; Biogenic emission; chemo-taxonomy; isoprene; Mediterranean Region; Monoterpenes; oak taxonomy; oaks; Quercus; terpenoid emissions; trace-gas exchange; volatile organic compounds (VOCs)